Computational analysis of CpG island distribution in human EEF1A2 gene encoding a putative oncoprotein implicated in ovarian and breast cancer - Permphan Dharmasaroja (2018)
The tissue-specific translation elongation factor eEF1A2 was recently shown to be a potential oncoprotein that is overexpressed in human ovarian and breast cancer. eEF1A2 encoded on chromosome 20 shares similar features to the nearubiquitously expressed eEF1A1, a closely-related isoform encoded on chromosome 6. It is still unknown why the tissuespecific eEF1A2 should have oncogenic properties in tissues in which eEF1A1 is already present at high levels. Abnormal methylation of CpG islands can lead to changes in expression of genes resulting in cancer growth and metastasis. In the present study, recently-developed and more stringent criteria for CpG islands, as being a DNA sequence longer than 500 bp with a G + C content equal to or greater than 55% and observed CpG/expected CpG of 0.65, were used to analyze CpG islands distribution in EEF1A1 and EEF1A2. Under these criteria, two CpG islands were identified in EEF1A1: one with an Alu repeat located in the promoter region and one without Alus, which spanned exon 1 and exon 2 and overlapped the transcription start site. In contrast, three out of four CpG islands in EEF1A2 were located in the exonic regions (exons 3, 4, 7 and 8), and none of them overlapped the transcription start site. Differences in the number and distribution of CpG islands, including the presence or absence of Alu repeats, in EEF1A1 and EEF1A2 may explain their differential expressions in certain cancer cells. © 2009 IEEE.